Levels of use of selected components of the Comprehensive Basic Nursing Programme - N. S. Gwele (AOSIS, 1996)
Change in nursing education in South Africa has been characterised by the predominance of the use of power-coercive strategies to effect change. Changes in nursing curricula are legislated through the South African Nursing Council. The Comprehensive Basic Nursing Programme (CBNP) became mandatory for all institutions offering basic professional nurse preparation education programmes in this country in 1985. This was a comparative descriptive study aimed at examining the levels of use of 47 nurse educators at four nursing colleges regarding their behaviours and skills in implementing four selected components of the CBNP. The components of the CBNP which formed the focus for this study were teaching to produce nurses capable of (a) rendering comprehensive health care, (b) nursing holistically, (c) thinking critically, and (d) learning independently.